Performance Investigation of the Savonius Wind Turbine by Putting a Rotating Cylinder in the front of Advancing by Varying the Diameter and Stagger Angle - Priyo Agus Setiawan; Subagio Soim; Bambang Antoko; Projek P. S. Lukitadi; Emie Santoso; Nopem Ariwiyono; Daisy D. K. R. Antariksih; Ammaisarah Disrinama (International Journal of Marine Engineering Innovation and Research, 2024)
The wind energy is the one of the renewable energy to produce the power using turbine. The Savonius turbine have lower performance compared to the other. In this work, the method used is the experimental stu using the wind tunnel to flow air go to the Savonius turbine. The model used is a conventional Savonius wind turbine by adding cylinder installed in front of advancing area with a diameter of 0.4 m and a height of 0.4 m and ds/d of 0.1, 0.2, 0.3, and 0.4 with the rotation of 20 rpm at a stagger angle of 0°, 30°, 60°, and 90°. The experiment is kept constant at the velocity of 7 m/s. This work objective will determine the torque and power coefficient by varying the diameter and stagger angle. The results show that the biggest performance decreased was about 40% in the variation of ds/d of 0.3 with a stagger angle of 0°. The best results show that the wind turbine performance occurred the highest improvement in about 12% at the variation of ds/d = 0.4 with a stagger angle of 60°.